EFFECTIVENESS OF USING INTERACTIVE METHODS IN TEACHING FOREIGN LANGUAGES - Irgashev Maxmud Usmonovich , Odilova Nazokatxon Abdulxamid qizi , Usmonova Shoiraxon Ruzievna , Egamberdiyeva Dildora Usubjonovna (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
It is known that the organization of the learning process is mainly one-sided, that is, carried out by the teacher. This, in turn, limits the ability of students to think independently and think creatively. Interactive lessons encourage students to master the content of education while developing their own critical and logical thinking. Efforts are made to ensure that no student is left unattended during the lesson. They will be able to openly express what they see, know and think. This ensures the effectiveness of interactive lessons. This is because the teacher-student collaboration contributes to a deeper understanding of the lesson content. Such situations provide mutual sincerity and interest in learning new knowledge.